Geological and geochronological constraints on the genesis of the giant Tongkuangyu Cu deposit (Palaeoproterozoic), North China Craton. Issue 2 (25th January 2016) - Liu, Xuan; Fan, Hong-Rui; Santosh, M.; Yang, Kui-Feng; Qiu, Zheng-Jie; Hu, Fang-Fang; Wen, Bo-Jie
ABSTRACT: The Zhongtiao Mountain region is endowed with some of the largest Cu deposits in northern China, among which the Tongkuangyu Cu deposit contains 70% of the total reserves of copper. The orebodies in this deposit are confined to metamorphosed volcanic tuff and monzogranitic porphyry which are enclosed within metasediments. Metamorphism and deformation resulted in intense modification of the deposit, leading to debates surrounding its genesis. In this study, we investigate the lithology, hydrothermal alteration, and mineralization in the deposit. Secondary ion mass spectrometer and laser ablation ICPMS zircon U–Pb dating show that the meta-monzogranitic porphyry was emplaced contemporaneous with the surrounding lithologies at 2180–2190 Ma as a sill, and that the basic volcanic rocks erupted slightly earlier at ~2220 Ma. The Re–Os geochronological data on molybdenite from the deposit constrain the timing of copper mineralization to 2122 ± 12 Ma. Together with published information from previous studies on this region, we infer that during ~2100–2200 Ma the Zhongtiao Mountain region experienced continental or back-arc rifting. We exclude a porphyry copper model for the deposit and favour sediment-hosted stratiform explanation for this deposit.